Rheological Properties of Wheat Flour (Triticum aestivum L.) Doughs as Affected by Inclusion of Decorticated Pigeon pea (Cajanus cajan L.) Flour and Protein - Hassan, Hayat A.; Mustafa, Abdelmoniem I.; Ahmed, Abdelhalim R. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
The objective of this study was to investigate the rheological properties of wheat flour(Triticum aestivum L.) doughs affected by the incorporation of decorticated pigeon pea(Cajanus cajan L.) flour (DPPF) and pigeon pea protein isolate (PPPI) aiming the productionof bakery products. Ratios of DPPF (0, 5, 10, 15, 20 and 25%) and PPPI (adjusted to raise theprotein levels to 15, 20 and 25%) incorporated in two types of wheat flours (extraction rate72%); for bread (BrWF) and biscuit (BsWF). Farinograph, Extensograph and Fermentographof wheat and composite flour doughs were studied. The Farinograms showed that the waterabsorption values for the composite BrWF/DPPF and BsWF/DPPF were found to range from65.1 to 65.9 % and 61.6 to 63.7%; dough development time from 4.0 to 5.0 min. and 4.0 to 4.4min. dough stability from 2.4 to 4.0 and from 2.3 to 4.1 min. for DPPF different ratios